Assessment of Economic Situation and Its Alterations According to the Basic View of Continuity - Giovanni Antonio Cossiga (Current Topics on Business, Economics and Finance Vol. 1, 2023)
The troubles affecting the economy, including those caused by the COVID 19, must be interpreted under the sign of the instability of systems, while following the natural tendency to recover the compatibility with nature. Even the economic cycle can be interpreted as natural tools for restoring development equilibrium. According to this viewpoint, the financial crises of the 2000s were symptoms of a serious gap between us and the irreversible obligation to system stability. On this topic, we will try to determine whether the financial tsunami caused by financial crises is the consequence of an ambiguous and abnormal secondary financial cycle that overlaps with the economic cycle. Therefore, it doesn’t seem unlikely that the breakdown imposed by the pandemic on the global economy could have the effect of blocking, but only temporarily, the development of the secondary financial cycle. The hypothesis we propose is that it’s the serious phenomenon of the unusual concentration of wealth and income, to the detriment of the rest of the community, the improper engine of the adverse financial cycle. It is adverse because it falls on the economy and once again is inflicting a heavy damage on the weaker part of the community.